Preparation of Lignin Carbon/Zinc Oxide Electrode Material and Its Application in Supercapacitors - Guo, Gaijuan (Molecules, 2021)
In this paper, carbon/zinc oxide (LC/ZnO) composites were successfully synthesized and characterized by X-ray powder diffraction, field emission scanning electron microscopy, Fourier transform infrared spectroscopy, Raman, thermogravimetry, and N(2) adsorption–desorption, and tested by electrochemical performance. Studies have shown that the morphology of LC/ZnO composites is that lignin pellets are embedded in ZnO microplates. The lignin carbon in the composites mainly exists in an amorphous structure, and the specific surface area and pore channels of metal oxides are increased by the presence of lignin carbon. The electrochemical performance test shows that the carbonization temperature of LC/ZnO with the highest specific capacitance is 550 °C, and the capacitance retention rate reaches 96.74% after 1000 cycles of testing, indicating that the composite material has good cycle stability. Compared with the control group, it is found that the specific capacitance of LC/ZnO-550 °C is 2.3 times and 1.8 times that of ZnO-550 °C and LC-550 °C, respectively. This shows that during the electrochemical test, the lignin carbon and the metal oxide promote each other and act synergistically. In addition, the composite material exhibits the characteristics of a pseudo-capacitance capacitor, indicating that the redox reaction occurred in the electrochemical performance test.